Toward Academic Excellence: Integrating Quality Management Strategies in Leading Madrasas' Development - Taj, Abu Bakar; Abidin, Achmad Anwar; Syahroni, Asep; Srinio, Fuad; Suyitno (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
Integrated quality management is a management approach that prioritizes student satisfaction and continually strives for improvement to foster a culture of quality in madrasas. It emphasizes attention to inputs, processes, and outputs to enhance student satisfaction. Against this backdrop, this research focuses on (1) the planning of integrated quality management for the development of exemplary academic madrasas at MAN 1 Jombang and (2) the implementation of integrated quality management in fostering the advancement of exemplary academic madrasas at MAN 1 Jombang. This research employs a descriptive qualitative methodology, utilizing data collection techniques such as interviews, observations, and documentation. The findings reveal that (1) the management planning at MAN 1 Jombang emphasizes student satisfaction through the provision of relevant learning materials, quality teachers, effective teacher-student interactions, and infrastructure development, and (2) the madrasa's leadership by focusing on its vision, mission, and goals, adopting strategic approaches, prioritizing performance, demonstrating strong commitment, and engaging in self-evaluation, contributes to enhancing the quality culture of the madrasa.